P‐193: Viewing Angle Performance of Curved Color‐by‐White AMOLEDs. Issue 1 (May 2017) - Kimmel, Jyrki; Bergquist, Johan; Kamada, Taisuke; Ito, Minato; Sakuishi, Tatsuya; Tamatsukuri, Yuki; Miyairi, Noriko; Nishido, Yusuke; Jimbo, Yasuhiro; Yokoyama, Kohei; Yamazaki, Shunpei
Abstract : Viewing angle performance of flexible organic light‐emitting displays (FOLEDs) with red‐green‐blue (RGB) side‐by‐side (SBS) architecture plays a major role in the visual appearance in the curved state. In particular, viewing the display from a central‐normal vantage point, the color shift becomes visible when viewing the bent edges of the display. The viewing angle performance of a color‐by‐white FOLED was measured goniometrically and compared with a SBS FOLED.